If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 59 = 12x + 11 Reorder the terms: 59 + 6x = 12x + 11 Reorder the terms: 59 + 6x = 11 + 12x Solving 59 + 6x = 11 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 59 + 6x + -12x = 11 + 12x + -12x Combine like terms: 6x + -12x = -6x 59 + -6x = 11 + 12x + -12x Combine like terms: 12x + -12x = 0 59 + -6x = 11 + 0 59 + -6x = 11 Add '-59' to each side of the equation. 59 + -59 + -6x = 11 + -59 Combine like terms: 59 + -59 = 0 0 + -6x = 11 + -59 -6x = 11 + -59 Combine like terms: 11 + -59 = -48 -6x = -48 Divide each side by '-6'. x = 8 Simplifying x = 8
| 3x^2-9x+20.25=21.25 | | q+14=8q+56 | | (2x+3)(x-1)=18 | | q+14=8q+8*7 | | x+12+8x=30 | | 7n+39=11n-13 | | u+4=4u-8 | | (2x+3)(x+1)=18 | | c+2c-5-5c=7 | | 3(2m-3)=8(m+1) | | x^3+5x^2+7x+35= | | 1.2(4x-3.2)=2 | | 2x-4(x+2)=x(2x-1) | | (7x+3)=6 | | 6C(12)=48 | | (7x+3)= | | (4x-10x)-40+3=2(x-1) | | 5z-4z=48 | | 1x=2x-7 | | 2x-37=24 | | 3x^2-x=5 | | X=2x-7 | | 2x-3y=24 | | 6t-6=9t-36 | | k^2+4k-77=0 | | -9.3x+1.8=-52.8-1.5x | | 3.5+2x+5.5=10 | | 4x-10x-40+3=2(x-1) | | 7x+3x=6 | | (7)m-(9)m=(-12) | | x^2+5x+10=0 | | 3(w-2)-6w=-21 |